2020
DOI: 10.4236/ojog.2020.1090114
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Neonatal Sepsis among Neonates Admitted at the Newborn Unit of Kenyatta National Hospital, Nairobi, Kenya

Abstract: Background: Neonatal sepsis is one of the primary causes of neonatal morbidity and mortality especially in developing countries. Despite the availability of different preventive interventions, in Kenya, the burden of neonatal sepsis remains critically high. Aim: To determine the prevalence and predictors of neonatal sepsis among newborns admitted at the newborn unit of Kenyatta National Hospital, Kenya. Methods: This is a hospital-based, cross-sectional study design carried out among 196 neonates and their mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
2
6
1
Order By: Relevance
“…The finding is in agreement with studies conducted in different parts of Ethiopia and other countries (30–36%) 4 , 11 17 . In contrast to our study, lower than 30% prevalence of neonatal sepsis was reported in Southeast Ethiopia 3 , India 18 ; and less than 20% prevalence was reported in Pakistan 13 , Ghana 19 , Uganda 20 , Kenya 21 , and Nepal 22 . We have noted that even higher prevalence of neonatal sepsis in Shashamane, Ethiopia (77.6%) 23 and Gondar, Ethiopia (64.8%) 23 .…”
Section: Discussioncontrasting
confidence: 99%
“…The finding is in agreement with studies conducted in different parts of Ethiopia and other countries (30–36%) 4 , 11 17 . In contrast to our study, lower than 30% prevalence of neonatal sepsis was reported in Southeast Ethiopia 3 , India 18 ; and less than 20% prevalence was reported in Pakistan 13 , Ghana 19 , Uganda 20 , Kenya 21 , and Nepal 22 . We have noted that even higher prevalence of neonatal sepsis in Shashamane, Ethiopia (77.6%) 23 and Gondar, Ethiopia (64.8%) 23 .…”
Section: Discussioncontrasting
confidence: 99%
“…This finding may be attributed to various factors among them is poor health care practice/management in both maternal and neonatal care or by environmental factors. Similar studies have been done in Kenya, for instance a study done at Kisii level five hospital (Muturi et al, 2018) found out a prevalence of 19.7% and at Kenyatta National Hospital a prevalence of 28.6% was reported (Geyt & Hauck, 2016;Okube & Komen, 2020). Both of these studies did indicate that maternal, neonatal and environmental factors were responsible for such prevalence.…”
Section: Discussionsupporting
confidence: 61%
“…For instance, in one study carried out in Ethiopia, the prevalence of neonatal sepsis among 351 neonates admitted in NICU Arbaminch general hospital Southern Ethiopia was 78.3% (Erkihun et al, 2019). In Kenya neonatal mortality rate by 2019 was at 21 deaths per 1000 livebirths (UNICEF, 2020) while prevalence of sepsis was estimated to be 28.6% at the new born unit of Kenyatta National hospital in central Kenya (Geyt & Hauck, 2016;Okube & Komen, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…11 Similar results could be the result of similarities in the research population and the time period in which the investigations were conducted. This finding, however, is significantly greater than that of research from Wolaita (33.8), 9 Gondar (64.8), 12 Kenya (28.6), 13 Uganda (11%), 14 Tanzania (31.4%), 15 and Nigeria (34%). 16 This disparity could be due to methodological differences, discrepancies, and variances in diagnostic modalities to confirm newborn sepsis.…”
Section: Discussionmentioning
confidence: 57%
“…This finding is in agreement with the findings from the study conducted in Debre Markos, Arbaminch general hospital, Ghana, Kenya, and Tanzania. 11,13,15,21,25 It is explained that preterm neonates tend to have poor host defenses and are more likely to suffer neonatal sepsis. Preterm infants may experience limited enteral feedings and/or exposure to breast milk, which collectively increase the risk for infection.…”
mentioning
confidence: 99%